1988
DOI: 10.1002/mrd.1120190107
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sperm creatine phosphokinase activity and sperm concentrations in normospermic and oligospermic men

Abstract: Toward the development of biochemical probes for the assessment of sperm function we have measured the activities of sperm creatine-N-phosphotransferase (CPK). There was a highly significant inverse correlation (P less than 0.001 in all comparisons) between sperm CPK activities and sperm concentrations in specimens of normospermic and oligospermic men with greater than 30 million sperm/ml (0.106 +/- 0.01 SEM, N = 90, expressed as CPK U/100 million sperm), 20-30 million sperm/ml (0.333 +/- 0.07 SEM, N = 30) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 15 publications
10
51
0
Order By: Relevance
“…Our findings for diaphorase activity are similar to those reported for some other sperm enzymes participating in the transport of energy, such as creatine kinase [7] and adenylate kinase [3], for which no relationship between the percentage of motile sperms and enzyme activity was found.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings for diaphorase activity are similar to those reported for some other sperm enzymes participating in the transport of energy, such as creatine kinase [7] and adenylate kinase [3], for which no relationship between the percentage of motile sperms and enzyme activity was found.…”
Section: Discussionsupporting
confidence: 88%
“…CK-BB and CK-MiMi in sperm were reported by Claus et al [2]; CK-BB and CK-MM were reported by Huszar et al [3][4][5]. Our results showed that CK-BB was not observed, but CK-MM and a trace amount of CK-MB were observed.…”
Section: Discussionsupporting
confidence: 66%
“…For CK, largely four groups of isoforms are present: CK-MM, CK-MB, CK-BB, and CK-MiMi. CK-MM is present in muscle cells, CK-MB in myocardial cells, CK-BB in cerebral cells, and CK-MiMi chiefly in mitochondrial inner membrane [2][3][4][5]. Sperm moves using ATP as an energy source and has a high-energy transportation mechanism, phosphorylcreatine shuttle, similar to other cells in mitochondria of its midpiece to the tail portions [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of these biochemical parameters is the concentration of the enzyme creatine phosphokinase (CK) in sperm, which reflects cytoplasmic retention, the hallmark of diminished maturity [3][4][5]. The CK immunocytochemistry studies of individual spermatozoa have also demonstrated a relationship between cytoplasmic retention and aspects of abnormal sperm morphology, including larger head size, roundness of the head, and increased proportion of amorphous heads.…”
Section: Introductionmentioning
confidence: 97%